Sowiecki system polityczny: transformacja albo degeneracja - Brzeziński, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
In the paper the author recalls his analyses of the character of the Soviet Union highest leadership, published in 1960. In the author’s opinion Lenin was a charismatic leader. In the period of the Stalin’s dictatorial regime the power was larger and larger bureaucratically institutionalized, with the decision-making centralized within his own secretariat. That bureaucratization was the reason why Stalin who did not possess the Lenin’s charisma was able to achieve the authority of the leader of world communism, albeit in fact he was an oriental despot rather than a revolutionary tribune. Nikita Khrushchev as a party leader ceased to be the main ideologist of party and was not a technical, administrative or economic expert. Therefore, the specialization of functions in the party leadership became something natural. After the overthrow of Khrushchev’s power the differentiation of these functions was considered standard, whereas charisma became a source of suspicions. Consequently, so-called apparatchiki attained the power. According to the author, the existence of “clusters of creativity” decides the vitality of political system. The lack of such clusters was the reason why in the Soviet system of leadership under Brezhnev there appeared symptoms of degeneration. The author thinks that today’s China may potentially be faced with the problems concerning the vitality of political system, which were characteristic of the Soviet Union.
Keywords: Związek Radziecki; Lenin, Vladimir Il'ič (1870-1924); Stalin, Iosif (1878-1953); Hruŝëv, Nikíta Sergéevič